Behavioral Consultation and Primary Care A Guide to Integrating Services - Robinson, Patricia J.; Reiter, Jeffrey T.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
"In this 2nd edition, Robinson and Reiter give us an updated blueprint for full integration of behavioral health and primary care in practice. They review the compelling rationale, but their real contribution is telling us exactly HOW to think about it and how to do it. This latest book is a must for anyone interested in population health and the nuts and bolts of full integration through using the Primary Care Behavioral Health Consultation model." Susan H McDaniel Ph.D., 2016 President, American Psychological Association Professor, University of Rochester Medical Center The best-selling guide to integrating behavioral health services into primary care is now updated, expanded and better than ever! Integration is exploding in growth, and it is moving inexorably toward the model outlined here. To keep pace, this revised text is a must for primary care clinicians and administrators. It is also essential reading for graduate classes in a variety of disciplines, including social work, psychology, and medicine. This updated edition includes: A refined presentation of the Primary Care Behavioral Health (PCBH) model The latest terms, trends and innovations in primary care Comprehensive strategies and resource lists for hiring and training new Behavioral Health Consultants (BHC) Step-by-step guidance for implementing the PCBH model A plethora of evolved practice tools, including new Core Competency Tools for BHCs and primary care providers Sample interventions for behaviorally influenced problems The use of "Third Wave"behavior therapies in primary care Detailed program evaluation instructions and tools The latest on financing integrated care An entire chapter on understanding and addressing the prescription drug abuse epidemic Experienced guidance on ethical issues in the PCBH model Improved patient education handouts With all of the changes in health care, the potential for the Primary Care Behavioral Health (PCBH) model to improve primary care-and the health of the population-is greater than ever. This book should be the first read for anyone interested in realizing the potential of integration.
Part I: The Perfect Storm of Primary Care -- Behavioral Consultation and Primary Care: The "Why Now?" and "How" -- A Primer on Primary Care -- Part II: The New Primary Care Team -- Recruiting and Training a Behavioral Health Consultant -- Behavioral Health Consultant Services, Location and Support -- Behavioral Health Consultant Core Competencies -- PCP and RN Competencies -- Part III: Making a Difference -- Theory and Action -- PCBH Program Evaluation -- Part IV: Let the Adventure Begin -- Practice Tools for the Behavioral Health Consultant -- Starting Up and Growing Up -- A Day in the Life of a Behavioral Health Consultant -- Pathway and Group Services -- Part V: Addressing the Challenges -- Common Ethical Issues -- Prescription Drug Abuse in Primary Care -- Challenging Moments: Provider, Patient and System.
Keywords: Psychology, Clinical; Emergency medicine; Family medicine; Clinical Psychology; Primary Care Medicine; General Practice / Family Medicine; Health Psychology